(untitled) (Research, Society and Development, 2023)
The objective of this study was to describe the process and analysis of hospitalizations and deaths resulting from diseases of the musculoskeletal system and connective tissue, in the state of Paraná, through the database of the Unified Health System, DATASUS, observing the epidemiological pattern. Data were extracted from hospitalization authorizations from January 2022 to January 2023, in Paraná. Data referring to 19,114 hospitalizations and 89 deaths were processed through a cross-sectional study using data from the DATASUS platform. They were described as frequencies of hospitalizations, and deaths, with analysis of patterns. The intra- and inter-rater reliabilities were 100%. Note that in January 2022 there were 1127 admissions, the lowest amount in the analyzed period, and the highest amount in August 2022, totaling 1663 admissions. There was a greater tendency for hospitalization cases in the eastern macro-region in proportion to the number of hospitalizations, with approximately 40.4% of cases in the analyzed period. The analyzed deaths analyzed in terms of gender, male (M) and female (F), there is a relationship - respectively - 1.47:1. The reliability and viability of the optimized routines were evidenced, suggesting the use of the Hospital Information System files as a source of data for the continuous evaluation of hospitalizations and deaths by the Unified Health System. A constancy observed in the proportions may have occurred due to the pattern of diagnoses, treatments and evolution of the clinical picture.